Keputusan investasi, Keputusan Pendanaan dan Kebijakan Dividen Sebagai Determinan Nilai Perusahaan - Heri Setiyo Cahyono; Ardiani Ika Sulistyawati (Universitas Muhammadiyah Metro, 2017)
Optimization of the company's value can be achieved through the implementation of the financial management function, where the financial decisions taken will affect other financial decisions and have an impact on the value of the company's financial management regarding the settlement of the important decisions taken by the company. This study aimed to analyze the influence investment decisions, financing decisions and dividend policy on the value of companies listed on the Indonesia Stock Exchange.Population in this research are manufacturing companies listed on the Stock Exchange from 2010-2013. After the selection of samples by purposive sampling method obtained a sample of 44 observations for four years. The research data was obtained from the published annual reports and stock price data downloaded from www.finance.yahoo.com. The analysis tool used is multiple linear regression and hypothesis testing is done by using the coefficient of determination, F test and t test. The data were processed using SPSS.From the test results can be seen that the variable dividend policy does not affect the value of the company, while variable investment decisions and funding decisions, significantly influence the value of the company. Adjusted R² values obtained of 0.250 or 25%. This shows a 25% coefficient value of the company was affected by investment decisions, financing decisions and dividend policy, while the other 75%, explained by other variables outside the model performed in this study Keywords: Investment Decisions, Decisions Financing, Dividend Policy and Corporate Values.